Efektivitas Daya Hambat Ekstrak Lidah Buaya (Aloe vera) Terhadap Pertumbuhan Bakteri Staphylococcus aureus Dengan Metode Difusi: The Effectiveness Of Aloe Vera Extract On The Growth Of Staphylococcus aureus Bacteria Using Diffusion Method - Hidayani, Al; Sukmawati, Vina Anggraini; Rahmah, Windya Nazmatur (Borneo Journal of Medical Laboratory Technology, 2024)
Staphylococcus aureus is one of the gram-positive bacteria that causes infection in the world. Extracts from the aloe vera plant contain several ingredients, one of which is saponins, anthraquinones, and tannins. This type of research is an experiment with a laboratory observation approach because the researcher only wants to know the effectiveness of the inhibition of aloe vera extract as a natural antibiotic on the growth of Staphylococcus aureus bacteria by diffusion method. Researchers used concentrations of 75%, 50% and 25% in the diffusion method. The results showed that the average resistance obtained at a concentration of 25% was 7 mm, a concentration of 50% and 75% was 0 mm (Negative). So based on the category according to CLSI the inhibitory ability of aloe vera (Aloe vera) extract against the growth of Staphylococcus aureus bacteria is resistant, which means that aloe vera (Aloe vera) extract at concentrations of 25%, 50% and 75% is not able to inhibit the growth of Staphylococcus aureus bacteria.